The use of the species Triticum petropavlovskyi Udacz. et Migusch. to expand the genetic diversity of spring bread wheat - A. E. Druzhin; S. N. Sibikeev; L. V. Andreeva (Труды по прикладной ботанике, генетике и селекции)
Background. The species Triticum petropavlovskyi Udacz. et Migusch. has a number of positive traits, but has rarely been used in breeding programs to improve bread wheat cultivars. The introgression of genetic material from this species into the Triticum aestivum L. gene pool will not only expand the genetic diversity of bread wheat with a set of traits valuable for breeders, but also help to analyze the expression of genes from T. petropavlovskyi in a new genetic environment. Materials and methods. Spring bread wheat lines L163 and L164 produced with the participation of bread wheat cv. ‘Voevoda’ and an accession of T. petropavlovskyi were target materials of the study. Conventional methods were applied to perform phenological, phytopathological, genetic, and bread quality evaluations. Statistical processing of the resulting data was carried out using the Agros-2.10 software. Results. L163 and L164 were studied for their morphological and phenological indicators, resistance to pathogens, productivity, and grain quality. Differences in a number of traits between the lines and the recipient cultivar were observed. The introgression of the T. petropavlovskyi genetic material into bread wheat showed both positive and negative effects on some agronomic characteristics. L163 was identified for its resistance to the pathogens of leaf rust and powdery mildew, and tolerance to cereal aphids. It combined high productivity with an increased grain protein content compared to the recipient cultivar. In addition, this line demonstrated good rheological properties of its dough. Conclusion. Merging genetic materials from T. petropavlovskyi and bread wheat cv. ‘Voevoda’ made it possible to produce lines with a set of positive characteristics. The selected line, L163, combined effective resistance to a number of diseases, high grain productivity, and good breadmaking qualities, so it was included in the breeding process.